Trial by Dutch laboratories for evaluation of non‐invasive prenatal testing. Part I—clinical impact. (15th November 2016) - Oepkes, Dick; Page‐Christiaens, G. C. (Lieve); Bax, Caroline J.; Bekker, Mireille N.; Bilardo, Catia M.; Boon, Elles M. J.; Schuring‐Blom, G. Heleen; Coumans, Audrey B. C.; Faas, Brigitte H.; Galjaard, Robert‐Jan H.; Go, Attie T.; Henneman, Lidewij; et al.
Abstract: Objective: To evaluate the clinical impact of nationwide implementation of genome‐wide non‐invasive prenatal testing (NIPT) in pregnancies at increased risk for fetal trisomies 21, 18 and 13 (TRIDENT study). Method: Women with elevated risk based on first trimester combined testing (FCT ≥  1:200) or medical history, not advanced maternal age alone, were offered NIPT as contingent screening test, performed by Dutch University Medical laboratories. We analyzed uptake, test performance, redraw/failure rate, turn‐around time and pregnancy outcome. Results: Between 1 April and 1 September 2014, 1413/23 232 (6%) women received a high‐risk FCT result. Of these, 1211 (85.7%) chose NIPT. One hundred seventy‐nine women had NIPT based on medical history. In total, 1386/1390 (99.7%) women received a result, 6 (0.4%) after redraw. Mean turn‐around time was 14 days. Follow‐up was available in 1376 (99.0%) pregnancies. NIPT correctly predicted 37/38 (97.4%) trisomies 21, 18 or 13 (29/30, 4/4 and 4/4 respectively); 5/1376 (0.4%) cases proved to be false positives: trisomies 21 ( n  = 2), 18 ( n  = 1) and 13 ( n  = 2). Estimated reduction in invasive testing was 62%. Conclusion: Introduction of NIPT in the Dutch National healthcare‐funded Prenatal Screening Program resulted in high uptake and a vast reduction of invasive testing. Our study supports offering NIPT to pregnant women at increased risk for fetal trisomy. © 2016 The Authors. Prenatal Diagnosis published by John Wiley & Sons, Ltd. © 2016 The Authors. Prenatal Diagnosis published by John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Non‐invasive prenatal testing (NIPT) for trisomies 21, 18 and 13 is mainly offered in a commercial setting. Offering NIPT to pregnant women at increased risk for fetal trisomy leads to a reduction in invasive testing. What does this study adds? NIPT implemented as a contingent test under the umbrella of a national health authority‐supported fetal trisomy screening program facilitates optimal counseling with close to 100% follow‐up, results in 86% uptake and confirms a major reduction of invasive tests.